Detection rate of specific antibodies to the HCV CORE+1 protein in “naive” cronically HCV-infected patients in depends on the stage of liver fibrosis and the HCV subtype - E. V. Lichnaya; M. A. Belopolskaya; V. N. Verbov; A. A. Yakovlev; A. V. Dmitriev; O. V. Kalinina (Журнал инфектологии, 2021)
Objective: The goal of this study was to examine the prevalence of anti-core+1 in “naive” patients with chronic hepatitis C and different stages of liver fibrosis infected by HCV subtypes 1b and 3a.Materials and methods: A total of 86 “naive” patients (37 men and 49 women) with CHC observed in the Botkin infectious disease hospital in 2017, were included in this study. The average age was 50,7±2,7. Laboratory tests included ALT and bilirubin. In 53 patients, the fibrosis stage in the liver tissue was evaluated by the TE method using Fibroscan (Echosens, France). The presence of antibodies to the core+1 protein in blood serum samples was determined by the “inhouse” indirect ELISA method using synthetic peptides F10 and F13, which amino acid sequences correspond to the antigenic determinants of core+1 protein of the HCV subtypes 1b and 3a, respectively.Results: In total, anti-core + 1 were detected in 27 (31,4%) subjects. It has been shown that the detection rate of anticore+1 does not depend on the HCV subtype. The study has indicated no statistically significant dependence between the presence of anti-core+1 and biochemical activity es of the infectious process (ALT, bilirubin). Anti-core+1 were detected in patients with all stages of fibrosis, however, the detection rate of anti-core+1 was statistically higher in patients with stage F4 fibrosis than in patients without liver fibrosis.Conclusion: The obtained results suggest a possible role of the core+1 protein in the development of fibrosis. In the natural course of HCV infection, the detection of anti-core+1 can be considered as a prognostic marker for the progression of fibrosis in the liver tissue.